Fernandinos of Yesteryear - Valdizán, Hermilio (1919)
Alzábase in the angle between the square of Santa Ana and Calle Santa Ana Sacraments, an old house facade always dusty, the windows always closed and eternally whimsical offering mutilation of their glassware. Nothing more picturesque than the facade of this old mansion whose architecture spoke of other times, other people and other interests; nothing more picturesque than the motley collection of businesses, if we may call them so, established under the moth-eaten and faded old house roofs; a small cafe stays busy impertinent and foul-mouthed drunks; an inn whose income dábanse slapping on a small table covered with white napkin doubtfully, a Genoese noodle recipe and a recipe Lima kebabs. And amid these precincts forever stale air, air that said alcohol and snuff onion, One would have a door, a large door that opened into vaulted and old copper yard wide corridor and whose pebbles extendíase the green carpet fungi and algae are difficult to classify. It was the Faculty of Medicine of Lima, was the Royal College of Medicine and Surgery of San Fernando and had also been when Republican enthusiasm made us deny anything that might smell like royalty, "Association Independence".